Review: Fifty Years Plus of Accelerometer History for Shock and Vibration (1940–1996) - Patrick L. Walter (Shock and Vibration)
This article summarizes the history of accelerometer development and the subsequent evolution of the commercial accelerometer industry. The focus is primarily on piezoelectric and piezoresistive accelerometers, although early resistance-bridge-type accelerometers are also described. The pioneer accelerometer manufacturing companies are identified and a chronology of technology development through today is presented.